2020
DOI: 10.1097/aud.0000000000000844
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Cochlear Implant Channels With Relatively Poor Electrode-Neuron Interfaces Using the Electrically Evoked Compound Action Potential

Abstract: Objectives: The primary objective of this study was to quantify local (within ear) and global (between ear) variation in the cochlear implant (CI) electrode-neuron interface (ENI) using the electrically evoked compound action potential (ECAP). We tested the hypothesis that, within an ear, ECAP measures can be used to identify channels with presumed good and poor ENIs, which may be influenced by a combination of spiral ganglion neuron (SGN) density, electrode position, and cochlear resistivity. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…While general performance across participants did not correlate with IPG slope, it did correspond with which ear a CI user was performing better with (with a large IPG slope effect indicating better performance in the form of lower speech reception threshold). Other studies also found evidence that the IPG slope effect may relate to neural density in humans [ 21 , 33 , 35 ]. The study introduced here attempts to relate AGF characteristics to the individual differences and the general outcome of speech performance with Sequential, Paired and Triplet speech processing strategies.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…While general performance across participants did not correlate with IPG slope, it did correspond with which ear a CI user was performing better with (with a large IPG slope effect indicating better performance in the form of lower speech reception threshold). Other studies also found evidence that the IPG slope effect may relate to neural density in humans [ 21 , 33 , 35 ]. The study introduced here attempts to relate AGF characteristics to the individual differences and the general outcome of speech performance with Sequential, Paired and Triplet speech processing strategies.…”
Section: Introductionmentioning
confidence: 85%
“…ENI is influenced by neural health [number of healthy auditory nerve fibers, see 9 ], electrode position [ 10 ] and abnormal tissue/bone growth in the cochlea [ 11 ]. The following methods have been used to estimate ENI: detection thresholds with focused electrical fields [ 12 14 ], CT imaging data [ 12 , 15 , 16 ], psycho-physical tuning curves [ 15 ], intracochlear resistance estimated with electrical field imaging [ 14 ], polarity sensitivity [ 17 19 ] and electrically evoked compound action potential (eCAP) inter-phase gap (IPG) difference measurements [ 20 , 21 ]. While audiologists have some flexibility to set parameters in the programming software of each manufacturer, the time to find the right strategy and setting is untenable in most clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Human eCAP data suggest that the quality of the ENI differs between pediatric and adult CI populations. Specifically, multiple studies have demonstrated that children and young adults have larger eCAP AGF slopes than older CI users (Hughes et al 2001; Cafarelli Dees et al 2005; Brown et al 2010; Jahn & Arenberg 2020a, b; Shader et al 2020). Factors contributing to this group difference include, but are not limited to, between-group differences in demographic factors (e.g., chronological age, duration of deafness), as well as in hearing loss etiology (Nadol et al 1989; Nadol 1997; Bodmer et al 2007; Brown et al 2010; Makary et al 2011; Viana et al 2015; Wu et al 2019; Zarowski et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Because the cochlea is adult-sized at birth and we controlled for electrode array type (proxy for electrode-neuron distance), the lower thresholds most likely reflect healthier and higher-density spiral ganglion neuron populations in the children than in the adults. Findings from multiple studies using evoked potentials have also suggested that children have greater integrity of auditory neurons than adults (e.g., Brown et al, 2010; Jahn & Arenberg, 2020a, 2020b). Furthermore, studies using CT-imaging found no between-group difference in their estimates of poorly positioned electrodes between adults and children (Noble et al, 2017; Noble et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Single-channel auditory detection thresholds measured in response to spatially focused electrical fields (i.e., focused thresholds) have been shown to be sensitive to several aspects of ENI quality such as the electrode-to-modiolus distance (DeVries & Arenberg, 2018; Jahn & Arenberg, 2019; Long et al, 2014), intracochlear resistance (Jahn & Arenberg, 2019), and possibly neural health and/or density (DeVries et al, 2016; Goldwyn et al, 2010; Jahn & Arenberg, 2020a, 2020b). An electrode that is placed in a suboptimal position in the cochlea (i.e., relatively distant from auditory neurons) (DeVries et al, 2016; Jahn & Arenberg, 2019; Long et al, 2014) or that stimulates a population of degenerated or dead auditory neurons (Bierer, 2007; Shepherd & Javel, 1997), or a combination of the two, requires relatively high current levels to elicit auditory percepts.…”
Section: Introductionmentioning
confidence: 99%